The Philosophical Foundation of Intellectual Property Rights Protection - Setyaningsih Setyaningsih; Aline Gratika Nugrahani; Irene Mariane (Faculty of Law, Universitas Pekalongan, 2022)
The communal system that lives in Indonesian society creates a view and culture that seems to oppose the presence of IPR because of its individuality. Enforcement of IPR protection in Indonesia is still a big homework for the Indonesian government in the midst of the communality of Indonesian society. On the other hand, the pressure of large countries has triggered the imposition of IPR regulations in Indonesia. As a result, Indonesia always holds the status of priority watch list. This paper discusses the philosophical basis for IPR protection in accordance with the character of Indonesian society. This paper will also examine how religion views the concept of IPR protection. So that IPR can be well received and grow properly in Indonesia. The writing uses normative research methods. Finally, it can be concluded that the MUI fatwa which prohibits and forbids the use of Intellectual Property Rights belonging to others without permission, is a strong foundation to sensitize Indonesian society as a religious society that is very obedient to its religious teachings to comply with the protection of Intellectual Property Rights.